Respuestas
Respuesta dada por:
1
° Enunciado:
![3 - 0.5 {x}^{2} + 4 = 6 3 - 0.5 {x}^{2} + 4 = 6](https://tex.z-dn.net/?f=3+-+0.5+%7Bx%7D%5E%7B2%7D++%2B+4+%3D+6)
° Resolvemos:
![3 - \frac{1}{2} {x}^{2} + 4 = 6 3 - \frac{1}{2} {x}^{2} + 4 = 6](https://tex.z-dn.net/?f=3+-++%5Cfrac%7B1%7D%7B2%7D++%7Bx%7D%5E%7B2%7D++%2B+4+%3D+6)
![3 + 4 - 6 = \frac{1}{2} x 3 + 4 - 6 = \frac{1}{2} x](https://tex.z-dn.net/?f=3+%2B+4+-+6+%3D++%5Cfrac%7B1%7D%7B2%7D+x)
![1 = \frac{1}{2} x 1 = \frac{1}{2} x](https://tex.z-dn.net/?f=1+%3D++%5Cfrac%7B1%7D%7B2%7D+x)
![\frac{1}{2} x = 1 \frac{1}{2} x = 1](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B2%7D+x+%3D+1)
![\frac{x}{2} = 1 \frac{x}{2} = 1](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%7D%7B2%7D++%3D+1)
![\boxed{x = 2} \boxed{x = 2}](https://tex.z-dn.net/?f=+%5Cboxed%7Bx+%3D+2%7D)
° Resolvemos:
Preguntas similares
hace 9 años
hace 9 años
hace 9 años
hace 9 años